Fertilization with nitrogen and potassium in banana cultivars ‘Grand Naine’, ‘FHIA 17’ and ‘Nanicão IAC 2001’ cultivated in Ribeira Valley, São Paulo State, Brazil (Acta Scientiarum. Agronomy, 2017)
The ‘Grand Naine’ banana cultivar is grown around the world, but it is susceptible to black Sigatoka fungus. The ‘FHIA 17’ and ‘Nanicão IAC 2001’ cultivars have the potential to replace susceptible cultivars, but there is little information about their nitrogen and potassium nutritional requirements. This study aimed to identify the best fertilizer recommendation with N and K for banana cultivars ‘FHIA 17’, ‘Nanicão IAC 2001’, and ‘Grand Naine’. The applied fertilizer levels with N and K2O in two production cycles were as follows: NK0, without fertilization; NK1, 175 N and 285 kg K2O ha-1 year-1; NK2, 350 N and 570 kg K2O ha-1 year-1; and NK 3, 525 N and 855 kg K2O ha-1 year-1. It was concluded that the N and K fertilization levels influenced most of the phenological and production parameters of ‘Grand Naine’ and ‘Nanicão IAC 2001’. ‘Nanicão IAC 2001’ and ‘Grand Naine’ achieved maximum yield with an application of 525 kg N ha-1 year-1 and 855 kg K2O ha-1 year-1. The ‘FHIA 17’ cultivar showed a low response to nitrogen and potassium fertilization. Regardless of cultivars, to achieve maximum productivity (44.2 and 43.3 ton ha-1 year-1), an application at 150% and 124% of the fertilizer recommendation is required in the 1st and 2nd production cycles, respectively.